Cu2SnS3 thin-film solar cells fabricated by sulfurization from NaF/Cu/Sn stacked precursor. (1st April 2015) - Nakashima, Mitsuki; Fujimoto, Junya; Yamaguchi, Toshiyuki; Izaki, Masanobu
Abstract: Cu2 SnS3 thin films were prepared by crystallization in a sulfur/tin mixing atmosphere from stacked NaF/Cu/Sn precursors deposited by the sequential evaporation of Sn, Cu elements, and NaF. The NaF mole ratio was changed at ( x = 0 to 0.12). From X-ray diffraction patterns and Raman spectra, the Cu2 SnS3 thin films were considered to have a monoclinic structure. The grain size of the Cu2 SnS3 thin films decreased with increasing NaF/Cu mole ratio. The band-gap energies of the Cu2 SnS3 thin films determined from quantum efficiency spectra were 0.93 and 1.02 eV. The solar cell with x = 0.075 demonstrated the best performance, namely, V oc = 283 mV, I sc = 37.3 mA/cm 2, FF = 0.439, and η = 4.63%.